Report of the Committee on Constitutional Amendments (House doc. (North Carolina. General Assembly. House of Commons) ;, 1852)
1852 Report of the North Carolina House Committee on Constitutional Amendments which disagreed with the Governor regarding free suffrage and other amendments to the North Carolina Constitution. The committee was wary of piecemeal changes to the constitution and concerned about the method to be used to make changes.